Practical evaluation guide : tools for museums and other informal educational settings - Diamond, Judy; Horn, Michael (Michael Stephen); Uttal, David H. (David Henry), 1960- (American Association for State and Local History book series., 2016)
Administrators of museums and other informal-learning centers often need to demonstrate, in some tangible way, the effectiveness of their institutions as teaching tools. Practical Evaluation Guide discusses specific methods for analyzing audience learning and behavior in museums, zoos, botanic gardens, nature centers, camps, and youth programs. The Practical Evaluation Guide is an all-in-one resource to guide professionals working in museums and other informal educational institutions. This new edition includes updates throughout and features a brand-new chapter on evaluating digital interacti.